2020
DOI: 10.3390/jcm9041035
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations Associated with the Overall Survival and Recurrence Free Survival among Oral Squamous Cell Carcinoma Patients

Abstract: Oral squamous cell carcinoma (OSCC) is a fatal disease caused by complex interactions between environmental, genomic, and epigenetic alterations. In the current study, we aimed to identify clusters of genes whose promoter methylation status correlated with various tested clinical features. Molecular datasets of genetic and methylation analysis based on whole-genome sequencing of 159 OSCC patients were obtained from the The Cancer Genome Atlas (TCGA) data portal. Genes were clustered based on their methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…It is commonly believed that epigenetic changes, such as DNA methylation, can drive abnormal gene expression of crucial genes involved in the development and progression of cancer, including head and neck cancer 35 . Hypermethylation of tumor suppressor genes and hypomethylation of proto-oncogenes at the promoter sites are associated with carcinogenesis and progression of OSCC 36 , 37 . For example, several studies have suggested that hypermethylation of PAX1 and ZNF582 genes is associated with aggressive progression and poor survival 38 40 .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that epigenetic changes, such as DNA methylation, can drive abnormal gene expression of crucial genes involved in the development and progression of cancer, including head and neck cancer 35 . Hypermethylation of tumor suppressor genes and hypomethylation of proto-oncogenes at the promoter sites are associated with carcinogenesis and progression of OSCC 36 , 37 . For example, several studies have suggested that hypermethylation of PAX1 and ZNF582 genes is associated with aggressive progression and poor survival 38 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) of oral cavity is a fatal disease caused by complex interactions between environmental, genomic and epigenetic alterations [ 61 ]. Surgical resection with microscopically clear margins of the primary tumor and prophylactic or therapeutic clearance of the neck lymph nodes, followed by various reconstructive approaches, remains the fundamental treatment for Oral Squamous Cell Carcinoma (OSCC) with adjuvant therapy reserved for high-risk disease [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Am Process In Virtual Surgical Treatment Planning Surgicmentioning
confidence: 99%
“…The incidence of oral cavity cancer is estimated to increase by up to 40% by 2040, with a corresponding increase in mortality also predicted [2]. Oral cavity cancer is reportedly most common in South and Southeast Asia and some countries in southern Europe [3]. Histologically, oral cavity squamous cell carcinoma (OSCC) is by far the most frequent type of oral cavity cancer and accounts for more than 90% of cases.…”
Section: Introductionmentioning
confidence: 99%